2022
DOI: 10.3390/idr14010004
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Species and Antimicrobial Resistance of Clinical Isolates from Pediatric Patients in Yangon, Myanmar, 2020

Abstract: Antimicrobial resistance (AMR) is a concern in medical care for children who have high burden of infectious diseases. We investigated the prevalence of bacterial species and their susceptibility to antimicrobials of 1019 clinical isolates from pediatric patients in a tertiary-care hospital in Yangon, Myanmar for one-year period (2020). The most frequently recovered species was Escherichia coli, followed by Klebsiella pneumoniae and Staphylococcus aureus, all of which accounted for 43% of clinical isolates, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…However, varied MDR rates among E. coli and K. pneumoniae in hospital settings have been reported globally, where > 50 % MDR againt a considerable range of antibiotics has been observed in Kenya [54], [63], Portugal [69], Canada [70], and Nepal [41]. Despite their collection from similar setups, the varied resistance patterns exhibited by the studied isolates can be attributed to the frequency of speci c antibiotic administration, among other factors such as those reported previously [71], [72]. The lack of proper antimicrobial resistance surveillance and stewardship, compounded by inadequate testing and documentation capacity, may be responsible for the high resistance rates [10], [73].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, varied MDR rates among E. coli and K. pneumoniae in hospital settings have been reported globally, where > 50 % MDR againt a considerable range of antibiotics has been observed in Kenya [54], [63], Portugal [69], Canada [70], and Nepal [41]. Despite their collection from similar setups, the varied resistance patterns exhibited by the studied isolates can be attributed to the frequency of speci c antibiotic administration, among other factors such as those reported previously [71], [72]. The lack of proper antimicrobial resistance surveillance and stewardship, compounded by inadequate testing and documentation capacity, may be responsible for the high resistance rates [10], [73].…”
Section: Discussionmentioning
confidence: 74%
“…Proper surveillance mechanisms are imperative considering the intricate nature of antimicrobial resistance, especially in E. coli and K. pneumoniae, which are notorious sources of nosocomial infections [71], [75], [90]- [92]. Appropriate characterisation of resistance patterns and genetic traits in these enterobacteria may help rede ne treatment regimens and avert further exacerbation and distribution of resistant strains [93].…”
Section: Discussionmentioning
confidence: 99%
“…However, varied MDR rates among E. coli and K. pneumoniae in hospital settings have been reported globally, where >50% MDR against a considerable range of antibiotics has been observed in Kenya [ 57 , 65 ], Portugal [ 70 ], Canada [ 71 ], and Nepal [ 47 ]. Despite their collection from similar setups, the varied resistance patterns exhibited by the studied isolates can be attributed to the frequency of specific antibiotic administration, among other factors such as those reported previously [ 72 , 73 ]. The lack of proper antimicrobial resistance surveillance and stewardship, compounded by inadequate testing and documentation capacity, may be responsible for the high resistance rates [ 10 , 74 ].…”
Section: Discussionmentioning
confidence: 86%
“…Proper surveillance mechanisms are imperative considering the intricate nature of antimicrobial resistance, especially in E. coli and K. pneumoniae, which are notorious sources of nosocomial infections [72,76,[91][92][93]. Appropriate characterisation of resistance patterns and genetic traits in these enterobacteria may help redefne treatment regimens and avert further exacerbation and distribution of resistant strains [94].…”
Section: Discussionmentioning
confidence: 99%
“…The highest prevalence of S. aureus was found in pus and blood, similar to other studies. [18][19][20] The highest isolation rate of S. aureus in pus and blood in this study could be partly due to S. aureus is a normal flora of skin that can enter the body through cracks, abrasion, cuts, surgical incisions, burn, and intravenous catheter and causes pyogenic infection. 21 The antimicrobial susceptibility testing in the present study demonstrated high resistance profiles of S. aureus isolates.…”
Section: Discussionmentioning
confidence: 99%